2000
DOI: 10.1300/j002v30n01_06
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Several of the Most Common Family Structures on the Academic Achievement of Eighth Graders

Abstract: Over the last twenty-five years, researchers have become greatly interested in the effects of family structure on the academic achievement of children. The vast majority of these studies have focused on one or two family structures in their analysis. There remains, however, a considerable amount of debate about which of these family structures impacts the academic achievement of children the most. Using the NELS data set from the 1988-1992 period, the effects of seven family structure variables were examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
2
15
0
1
Order By: Relevance
“…2. Children of divorced parents are more likely to have lower grade point averages (GPAs) and be asked to repeat a year of school (Jeynes 2000). 3.…”
Section: Effects Of Divorce On Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Children of divorced parents are more likely to have lower grade point averages (GPAs) and be asked to repeat a year of school (Jeynes 2000). 3.…”
Section: Effects Of Divorce On Childrenmentioning
confidence: 99%
“…3. A study of eleven industrialized countries showed that children living in two-parent families had higher math and science scores (Jeynes 2000). 4.…”
Section: Effects Of Divorce On Childrenmentioning
confidence: 99%
“…As noted by Slade and Wissow (2007), the child's broader context is also important in understanding school outcomes. Socioeconomic indicators have frequently been found to impact school outcomes (Sirin, 2005), as well as family structure (Jeynes, 2000) and child ethnicity or race (Kao & Thompson, 2003). However it is likely that the effects of race are at least partially explained by the broader social context of education (Weinstein, Gregory, & Strambler, 2004) The purpose of this study was to examine predictors of reading level in a cohort of high-risk children.…”
mentioning
confidence: 99%
“…Recent research suggests that all three schools of thought are helpful to some degree in explaining the effects of parental family structure (Jeynes, 2000;McLanahan & Sandefur, 1994). Nevertheless, if one focuses on issues of causality, it appears that the access to parents school of thought probably explains the largest portion of the academic disadvantage that children of divorce face (Allison & Furstenberg, 1989;Jeynes, 1998b).…”
mentioning
confidence: 99%